Model of Brand Salience of Consumer Skincare Soap Products. Issue 2 (December 2019) - Menon, Balakrishnan
Brand salience is the eminence of a brand in the consumer memory and is linked to the brand choice and purchase by consumers. Brand salience is the brand's propensity to get noticed and influenced by consumers in buying situations. This research is aimed at proposing a model of brand salience for fast-moving consumer goods products, which incorporates brand awareness, brand salience, and brand image leading to the purchase intention. Brand awareness was measured with the dimensions of brand knowledge, brand recall, and brand association. Results of the data analysis conducted using partial least square method with structured equation modelling found empirical evidence of a model of brand salience where there was a significant relationship between brand salience and purchase intention. It was found that predominant brand awareness and brand image substantiated to building brand salience. The evidence supported building a primary brand salience to build the depth and breadth of the brand's associations in consumer memory. The practical implication of the study is that a marketer can build sufficient brand salience; it increases the probability of purchase intention, which in turn is the most important aspect for any company to increase product sales through enhanced customer equity, customer loyalty, and relationship marketing.